The Euclid Data Processing Challenges. Issue Volume 12:Issue S325(2016) (30th May 2017) - Dubath, Pierre; Apostolakos, Nikolaos; Bonchi, Andrea; Belikov, Andrey; Brescia, Massimo; Cavuoti, Stefano; Capak, Peter; Coupon, Jean; Dabin, Christophe; Degaudenzi, Hubert; Desai, Shantanu; Dubath, Florian; et al.
Abstract: Euclid is a Europe-led cosmology space mission dedicated to a visible and near infrared survey of the entire extra-galactic sky. Its purpose is to deepen our knowledge of the dark content of our Universe. After an overview of the Euclid mission and science, this contribution describes how the community is getting organized to face the data analysis challenges, both in software development and in operational data processing matters. It ends with a more specific account of some of the main contributions of the Swiss Science Data Center (SDC-CH).